Diagenetic evolution of the upper Cretaceous limestone and sandstone exhumed reservoirs in the western Basque–Cantabrian Basin, North Spain. (September 2015) - Permanyer, A.; Marfil, R.; Martín-Martín, J.D.; Estupiñán, J.; Márquez, G.; Arroyo, X.
Abstract: The Basque–Cantabrian Basin (NE Spain) has been considered one of the most interesting areas for hydrocarbon exploration in the Iberian Peninsula since the 60th to 70th of last century. This basin is characterized by the presence of numerous outcrops of tar sands closely associated with fractures and Triassic diapirs. The aims of this work is to establish the diagenetic evolution of the Upper Cretaceous reservoir rocks with special emphasis in the emplacement of oil and their impact on reservoir quality. The studied rocks are constituted of carbonates and sandstones that contain massive quantities of bitumen filling vugs and fractures. Petrographic results indicate that the carbonate rocks from Maestu outcrops are bioclastic grainstones and wackestones, whereas the tar sandstones from Atauri and Loza outcrops are dominated by quartzarenites and subordinated subarkoses. The paragenetic sequence of the main diagenetic phases and processes include, pyrite, bladed and drusy calcite cement, calcite overgrowths, silicification of bioclasts and microcrystalline rhombic dolomite cement, and first stage of oil emplacement, blocky calcite cement, coarse crystalline calcite cement, calcitized dolomite, calcite veins, saddle dolomite and stylolites filled by the second phase of oil entrance. Together with the above mentioned diagenetic alterations, the arenites are affected by early kaolinitization of feldspars and the scarce formation of clay rim and epimatrix of illite. All sandstones and dolomitized carbonate rocks show high intercrystalline and intergranular porosity which is full by biodegraded hydrocarbons (solid bitumen). The biodegradation affects alkanes, isoprenoids and partially hopanes and steranes saturated hydrocarbons. Aromatics hydrocarbons, like naphthalenes, phenanthrenes, dibenzothiophenes and triaromatics are also affected by biodegradation. Results indicate that the first HC emplacement corresponds to early stage of calcite and dolomite cementation, and the second and more important emplacement is related to fracturation processes resulting in the formation of excellent reservoirs. Highlights: We study exhumed reservoirs in calcarenites and arenites. Reservoir diagenetic evolution with emphasis in the emplacement of oil is discussed. First stage of oil emplacement took place after extensive early calcite cementation. Second stage of oil emplacement took place during uplift in relation to fractures.